The Role of Centella asiatica and Its Main Bioactive Compound, Asiatic Acid in Cardiac Remodeling: A Systematic Review of Animal Studies - Fadhillah, Muhamad Rizqy; Arozal, Wawaimuli; Wibowo, Heri; Bustami, Arleni; Primadhani, Suci Widya; Gusti Khatimah, Nurul; Putri, Rizky Clarinta; Riski Amanda, Clara; Azizah, Nur (Molecular and Cellular Biomedical Sciences, 2025)
Cardiac remodeling is a phenotype of heart failure characterized by a molecular, cellular, and interstitial change in the heart, which manifests in the change of size and function of the heart after specific insults with multiple mechanisms. Centella asiatica (CA) and its main bioactive triterpenoid, asiatic acid (AA), pose antioxidant and anti-inflammatory effects. Still, no adequate clinical trials support the potency of CA and AA as anti-cardiac remodeling. Hence, this systematic review aims to provide an in-depth analysis of CA extract and AA in animal studies' prevention or therapy of cardiac remodeling. The search strategies were conducted based on preferred reporting Items for systematic reviews and meta-analysis (PRISMA) protocol through Pubmed, EMBASE, Scopus, and Web of Science using keywords as follows: “Centella asiatica” OR “Asiatic Acid” AND “Cardiac Remodeling” OR “Cardiac Hypertrophy” OR “Cardiac Fibrosis” along with their synonym. The data collected included hemodynamic parameters based on echocardiography, biomolecular tests such as quantitative polymerase chain reaction (qPCR), Western blotting, or biochemistry procedures. The paper quality was assessed using Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) risk of bias (RoB). The previous selected study has shown that CA and AA might prevent and cure cardiac remodeling by inhibiting various pathways and protein expressions through AMPKα, NOX2/4, PI3K/Akt/mTOR, p70S6K, YAP/TAZ, and IL-1β, IL-6, and IL-18 cytokines. CA and AA, thus, exhibit cardioprotective effects in the animal model, which need to be confirmed in the clinical trials on humans. Keywords: cardiac remodeling, cardiac hypertrophy, cardiac fibrosis, Centella asiatica, asiatic acid